Curcumin protection against ultraviolet-induced photo-damage in Hacat cells by regulating nuclear factor erythroid 2-related factor 2. Issue 2 (20th December 2021) - Deng, Huiyan; Wan, Miaojian; Li, Huaping; Chen, Quan; Li, Runxiang; Liang, Bihua; Zhu, Huilan
ABSTRACT: Curcumin suppressed ultraviolet (UV) induced skin carcinogenesis and activated the nuclear factor erythroid 2-related factor 2 (Nrf2) pathway. However, whether curcumin protects skin injury caused by UV is still unknown. A vitro model was established and curcumin effects on Hacat cells were detected. Nrf2 was knocked down in Hacat cells to verify the Nrf2 role in the protective effect of curcumin. Results indicated that ultraviolet A (UVA) (or ultraviolet B (UVB)) irradiation would lead to decreased cell proliferation, increased cell apoptosis, decreased catalase, heme oxygenase 1, and superoxide dismutase expression, and increased levels of protein carbonylation and malondialdehyde (p < 0.05). These adverse events could be reversed by adding 5-μM curcumin. Meanwhile, we found that the application of curcumin effectively induced Nrf2 nuclear accumulation in Hacat cells. While in the Nrf2 knockdown cells, the protective effects of curcumin against UVA (or UVB) were attenuated. Conclusively, curcumin protects Hacat cells against UV exposure-induced photo-damage by regulating Nrf2 expression.